Influence of rice (Oryza sativa) habit groups and moisture conservation practices on soil physical and microbial properties in rice + lathyrus relay cropping system under rice fallows in Eastern Plateau of India - SINGH, R N; PRAHARAJ, C S; KUMAR, RAHUL; SINGH, S S; KUMAR, N; SINGH, UMMED (The Indian Journal of Agricultural Sciences, 2017)
The study involving bio-physical aspects of popular rice (Oryza sativa L.) + lathyrus relay system for conserving natural resources and deriving the best benefits out of them was carried out in a vertisols at Indira Gandhi Krishi Vishwa Vidyalaya, Raipur (India) during 2011-14. The study location comes under tropical sub humid climate that receives an annual precipitation of 1582 mm. Two rice habit groups (a tall local rice Masuri maturing at 140 days visà-vis a dwarf HYV of rice Swarna with 110 days duration) were combined with two moisture conservation practices (retaining rice stubble height up to 15 cm versus 30 cm) for growing two contrasting varieties of lathyrus (early high biomass accumulating Ratan vis-à-vis medium high biomass Prateek). The study showed that soil moisture depletion pattern was relatively lower in case of residue retention at a higher cutting height, i.e. 30 cm in comparison to 15 cm with better and higher crop cover in the former. At later stages of lathyrus, faster moisture depletion was observed in case of lathyrus Ratan over that in Prateek. Yet, maximum soil moisture depletion was recorded under Prateekespecially under long rice habit group since it stayed for long as compared to ‘Ratan’. Similarly, bulk density (BD) was increased slightly with both time and soil compaction as a result of tillage or soil traffic. Soil strength indicated higher order variation (0.13 to 0.19) which could explain relatively higher sensitivity of soil strength to relay cropping situation in comparison to BD. However, marginal changes did occur in respect of soil porosity (47- 50%), pH (6.6 to 7.2) and EC (0.12 to 0.14 dS/m) at 15 cm profile depth. Moreover, as a result of slow depletion of soil moisture storage (SMS) following stubble retained at 30 cm height, soil organic carbon (SOC) status was greatly enhanced under it. Similar small increments in respect of soil fertility attributes such as soil available N (193.4 to 210.4 kg/ha), soil-P (10.3 to 12.2 kg/ha), soil-K (465.4 to 475.4 kg/ha), Cu (2.2 to 2.5 mg/kg), Fe (6.9-7.6 mg/kg), Zn (0.69-0.84 mg/kg) and Mn (6.2-6.9 mg/kg) after the harvest of rice were observed with diverse treatment combinations. Similarly, soil microbiological properties such as Rhizobium, dehydrogenase activity, crop growth and nodulationdid affect following treatment imposition. Besides these, weed dynamics and the resultant yield attributes and grain yield were favoured especially in those treatments where soil moisture is conserved (higher SMS) and availability of it was extended over a period of time. Therefore, the study carried out in a lentil relayed with diverse rice habits showed that efficient management of soil and land resources was crucial for realizing higher output through adequate soil cover with better soil health.